2012
DOI: 10.1155/2012/328392
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Female Mate Preference and Species Isolation inDrosophila

Abstract: The processes that underlie mate choice have long fascinated biologists. With the advent of increasingly refined genetic tools, we are now beginning to understand the genetic basis of how males and females discriminate among potential mates. One aspect of mate discrimination of particular interest is that which isolates one species from another. As behavioral isolation is thought to be the first step in speciation, and females are choosy more often than males in this regard, identifying the genetic variants th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 145 publications
(177 reference statements)
0
31
1
Order By: Relevance
“…The same telomeric and centromeric regions on the 3rd chromosome that affect genital shape morphology here have also been found to affect mating behavior in D. simulans - D. mauritiana [25, 33] and D. simulans - D. melanogaster [34]. We can examine whether the different lobe morphology induced by the introgressions has an impact on mating behavior by testing the behavior of the introgression lines.…”
Section: Discussionmentioning
confidence: 72%
“…The same telomeric and centromeric regions on the 3rd chromosome that affect genital shape morphology here have also been found to affect mating behavior in D. simulans - D. mauritiana [25, 33] and D. simulans - D. melanogaster [34]. We can examine whether the different lobe morphology induced by the introgressions has an impact on mating behavior by testing the behavior of the introgression lines.…”
Section: Discussionmentioning
confidence: 72%
“…Despite pioneering efforts (Coyne et al, 1994; Hollocher et al, 1997; Laturney and Moehring, 2012; Manning, 1959; Mayr and Dobzhansky, 1945; Moehring et al, 2006; Nanda and Singh, 2012; Ritchie et al, 1999; Shirangi et al, 2009; Smadja and Butlin, 2009; Spieth, 1949; Sturtevant, 1920), little is known about the neural pathways that inhibit interspecies mating. Gr32a appears to function in foreleg neurons to inhibit interspecies courtship, consistent with the observation that D. melanogaster males tap potential mates early during courtship.…”
Section: Discussionmentioning
confidence: 99%
“…2009). Mate preferences have been shown to have a genetic basis in many animals (reviewed by Bakker and Pomiankowski 1995; within species: Jennions and Petrie 1997; among species: Laturney and Moehring 2012), and there is a growing evidence for the importance of sexual imprinting during early development. Experiments demonstrated that young birds, mammals, and fish cross-fostered to a related (sub)species develop sexual preferences for the foster mother's (sub)species (e.g., Clayton 1990; Kendrick et al.…”
Section: Introductionmentioning
confidence: 99%